PENGARUH INTELLECTUAL CAPITAL TERHADAP KINERJA PERUSAHAAN (Studi Empiris Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2017-2019) - Daud Riyadh Akbar; Moh Didik Ardiyanto (Diponegoro Journal of Accounting, 2021)
This study aims to examine the effect of intellectual capital on company performance. The variables used in this research are Human capital efficiency, Structural capital efficiency, Capital employed efficiency and Value added intellectual coefficient as independent variables as well as market value (Tobin's q), company productivity (ATO), sales growth (SG), company profitability ( ROA) as the dependent variable.This study uses a manufacturing company from 2017 to 2019 with a total sample of 150 samples. Sampling is based on a purposive sampling method that follows certain criteria. Multiple linear regression analysis is the analytical method used in this study.The results of this study indicate that human capital efficiency has no positive effect on market value, company productivity and sales growth. However, he found that human capital efficiency has a positive effect on company profitability. Structural capital efficiency affects the three dependent variables, namely market value, firm productivity and firm profitability. However, structural capital efficiency does not have a positive effect on sales growth. Capital employed efficiency has a positive effect on the two dependent variables, namely: the firm's market value and the company's profitability. However, capital employed efficiency does not have a positive effect on company productivity and sales growth of companies listed on the IDX. Value Added Iintellectual Coefficient does not have a positive effect on the three dependent variables, namely the company's market value, company productivity, and company sales growth. However, Value Added Iintellectual Coefficient has a positive effect on company profitability.